Estimativas de mortalidade materna de alguns fatores associados: Moçambique 2007 - Abdulai Dade (2013)
This study presents levels of maternal mortality and its association with selected factors. We used census data from Mozambique 2007, specifically information on deaths occurred at the household over the 12 months prior to the date of the Census. This information was evaluated and we established correction factor of 1.47 for the average number of maternal deaths reported. Maternal mortality measures are Maternal Mortality Ratio (MMR) maternal mortality rate, life time risk and proportion of maternal deaths at reproductive ages. Initially, descriptive analysis was carried out. Univariate and multivariate analysis was also developed to adjust the model that can explain the risk of maternal death in a household. The MMR for Mozambique, 2007, was defined to be around 901.5 deaths per 100 000 live births. The age pattern of the MMR followed the expected format, with the highest risk at the extreme ages and minor fluctuations due to expected variation that may happen with rare events as a maternal death. The Central region had the highest levels of maternal mortality; the Southern region showed the relatively minor risks. Regarding the provinces, estimates for Sofala province have the highest levels and Niassa the lowest ones. The results revealed a strong association between the risk of a maternal death in the household and social and economic variables relative to the households and households head (level of education, his/her status of speaking Portuguese, wealth quintile and condition of being employed). Demographic variables diminish importance as explicative factor to the risk of a maternal death as socioeconomic variables are incorporated in the model. That is, in terms of public policy, it is urgent to invest in socio-economic development of the family. It is of utmost importance for the improvement of our knowledge on population to monitor and follow-up the analytical results presented here. The reason is that resultsspecifically those related to maternal mortality, based on information collected in the Census related to deaths occurred at the household. We also conclude that despite the advances presented in this study on maternal mortality, the efforts made in terms of data collection are still unsatisfactory.